Neuroprotective Effects of Withaferin-A Nanoparticles on Scopolamine Rat Model of Alzheimer’s Disease - Subramanian, Madhu; Munuswamy, Komala; Pitchaimuthu, Pandian (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Alzheimer's Disease (AD) suffers from dementia more often in 65-year or older patients. Symptoms of AD's are linked to disease-causing neurons, and current pharmacological therapies inadequately regulate deadly outcomes. Withania somnifera (L), has been contributing as a traditional multifunctional herb with a wide variety of health benefits. Materials and Methods: This research examined the importance of Withaferin A nanoparticles against scopolamine induced neuron loss (Impair on memory). Five groups of 6 rats weighing 150-200 g were randomly split. Negative and positive control animals received 2mL/kg saline solution in groups 1 and 2. 3^rd and 4^th group received 5mg/kg of pure Withaferin-A and Withaferin-A nanoformulation. Group 5 received 10 mg/kg of tacrine as a normal medication. Except for group 1, all other groups were induced 30 min after drug administration with 1mg/kg scopolamine. EPM was used to understand the behavioral parameters. Results: Inflexion ratios of 1.1 and 1.3 were seen in groups treated with Withaferin-A nanoparticles and the conventional medication. AchE, MDA, GSH reductase were also measured. Compared to the pure drug, Withaferin-A nanoparticles exhibited substantial activity. Withaferin-A exhibits an anti-amnesic effect similar to tacrine at a specific level. Conclusion: Withaferin-A nanoparticles may help neurodegenerative disease. To establish the formulation as a standard AD's treatment, pharmacokinetic aspects should be explored.
Keywords: Withaferin-A; EPM; Brain enzymes; Inflexion ratio; Nano formulations